The Effect of Liquidity and Profitability on Share Prices (Case Study on Food and Beverage Companies Listed on Indonesia Stock Exchange) - Sri Haryani; Muhammad Ali; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
The purpose of this study was to determine and analyze the effect of liquidity and profitability on stock prices in food and beverage companies listed on the Indonesia Stock Exchange. The population in this study were 27 food and beverage industrial manufacturing companies listed on the Indonesia Stock Exchange. The sample used is 10 companies using the purposive sampling technique. Data were collected by means of observation, literature study, and documentation of liquidity (current ratio and earning per share) and profitability (return on investment and return on equity) and stock prices in food and beverage industry companies listed on the Indonesia Stock Exchange and analyzed by using multiple regression. The results showed that liquidity had no effect on stock prices, while profitability had a positive and significant effect on stock prices.